Achieving selective photocatalytic CO2 reduction to CO on bismuth tantalum oxyhalogen nanoplates. Issue 35 (19th May 2021) - Tao, Xiaoping; Wang, Yi; Qu, Jiangshan; Zhao, Yue; Li, Rengui; Li, Can
Abstract : Photocatalytic reduction of CO2 to selectively produce CO was realized on the semiconductor Bi4 TaO8 X (X = Cl, Br) under visible light without sacrificial reagent. Morphology regulation and silver cocatalyst decoration could enhance the activity. Abstract : The photocatalytic conversion of carbon dioxide to fuels presents great promise for storing renewable energy and alleviating global warming. Herein, using the visible-light-responsive semiconductor bismuth tantalum oxyhalogen (Bi4 TaO8 X, X = Cl, Br) with suitable band structures, we realize the photocatalytic reduction of CO2 to selectively produce CO under visible light without introducing any sacrificial reagents. An isotope-labeling experiment clearly demonstrated that the produced CO originated from CO2 and, additionally, continuous water oxidation for O2 evolution was also detected during photocatalytic CO2 reduction. Further introducing crystal morphology modulation to prepare well-defined nanocrystals enables great enhancement of the photogenerated charge separation performance compared to that of irregular nanoparticles. Moreover, surface modification of the silver nanoparticles deployed as the CO2 reduction cocatalyst evidently facilitates the generation of intermediate species to promote the surface catalytic reaction. This work not only presents a potential semiconductor candidate for photocatalytic CO2 reduction, but it also provides a feasible strategy for designing artificial photosynthetic systems via combining morphology tailoring and suitable cocatalysts.